(untitled) - Linsley, Ray K. (New York, 1972)
Gồm các mục sau: descriptive hydrology; quantitative hydrology; groundwater; probability concepts in design; water law; reservoirs; dams; spillways,gates,and outlet works; open channels; pressure conduits; hydraulic machinery; engineering economy in water-resources planning; irrigation; municipal and industrial water supply; hydroelectric power; river nivigation...
Keywords: Hydraulic engineering,Water resources development